Études techniques - collaborateurs, Divers (Assurances, 1985)
These studies bring together the comments of our contributors on unlimited liability insurance (automobile) as well as on the Audatex form, which helps to speed up claims settlements and facilitates the work of the estimate centres. Our contributors have more comments on insurable value. Mr. Michel Beaudoin looks at the new rapid action sprinkler heads. Finally, J.H. defines what in practice is known as operation profit or loss in insurance operations.